Knowledge, attitude and practices of clinical quality and performance assessment among emergency medical services personnel in South Africa: A mixed methods study. (2nd May 2019) - Howard, Ian; Cameron, Peter; Castrén, Maaret; Wallis, Lee; Lindström, Veronica
Abstract: Objective: Deficits in healthcare quality are becoming an increasing concern globally. Within the low‐ to middle‐income country (LMIC) setting insufficient quality has become a bigger barrier to reducing mortality than insufficient access, where 60% of deaths from conditions amenable to healthcare, are due to poor quality care. Measuring quality is key towards improving the effectiveness of healthcare in this setting. Methods: A mixed methods sequential‐explanatory study was conducted, to describe what Emergency Medical Service (EMS) practitioners understood about quality systems within the LMICs, using South Africa as an example. Part 1 consisted of a cross‐sectional survey ( n = 169), the results of which were utilised to develop a semi‐structured interview guide for Part 2. Interviews of participants from Part 1 explored the results of the survey ( n = 20) and were analysed through content analysis to develop core categories central to the understanding of quality assessment in the LMICs. Results: Despite relatively poor knowledge of organisational‐specific quality systems, understanding of the core components and importance of quality systems was demonstrated. The role of these systems in the LMICs was supported by participants, where the importance of context, system transparency, reliability and validity were essential towards achieving ongoing success and utilisation. The role of leadership and communication towards the effective facilitation of such a system was equally identified. Conclusion: Within EMS, quality systems are in their infancy. It could be argued that this is somewhat more pronounced in the LMICs, where knowledge of organisational quality systems was found to be poor. Despite this, there was a strong general understanding of the importance of quality systems, and the role they have to play in this setting.